Guatemala-U.S. migration : transforming regions - Jonas, Susanne, 1941-; Rodriguez, Néstor (University of Texas Press, 2014)
This comprehensive study of five phases of Guatemalan migration--both Maya and ladino--to the United States from the late 1970s to the present illuminates the transregional experiences of those who pass through Mexico.